2013
DOI: 10.1038/nature12783
|View full text |Cite
|
Sign up to set email alerts
|

Distinct fibroblast lineages determine dermal architecture in skin development and repair

Abstract: Fibroblasts are the major mesenchymal cell type in connective tissue and deposit the collagen and elastic fibers of the extracellular matrix (ECM)1. Even within a single tissue fibroblasts exhibit remarkable functional diversity, but it is not known whether this reflects the existence of a differentiation hierarchy or is a response to different environmental factors. Here we show, using transplantation assays and lineage tracing, that the fibroblasts of skin connective tissue arise from two distinct lineages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

70
1,168
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,022 publications
(1,285 citation statements)
references
References 31 publications
70
1,168
0
6
Order By: Relevance
“…Lrig1 and Dlk1 are expressed in the upper and lower dermis, respectively, during skin development. Those different populations have different hair follicle-regenerative abilities during reconstitution (32). In the present study, RNA-seq data showed that Dlk1 expression was quickly lost at day 1, and Lrig1 was decreased but was maintained at a certain level during culture, indicating that the dermal cells of the reconstituted skin originated from the upper dermis (SI Appendix, Fig.…”
Section: Molecular Perturbation Of the Skin Organoid Formation Processmentioning
confidence: 76%
“…Lrig1 and Dlk1 are expressed in the upper and lower dermis, respectively, during skin development. Those different populations have different hair follicle-regenerative abilities during reconstitution (32). In the present study, RNA-seq data showed that Dlk1 expression was quickly lost at day 1, and Lrig1 was decreased but was maintained at a certain level during culture, indicating that the dermal cells of the reconstituted skin originated from the upper dermis (SI Appendix, Fig.…”
Section: Molecular Perturbation Of the Skin Organoid Formation Processmentioning
confidence: 76%
“…It is generally believed that positional skin identity is regulated by epithelial (keratinocytes) and mesenchymal (fibroblasts) interactions. 1e5 Indeed, three-dimensional skin equivalent models and transplantation experiments show that epidermal stratification during the keratinocyte differentiation program is remarkably disrupted in the absence of fibroblasts, 2,4,5 demonstrating that epidermal development and homeostasis are regulated by extrinsic factors released by fibroblasts. Such interactions have been further clarified through an analysis of the differential localization of epidermal keratins in distinct epidermal layers and body sites.…”
mentioning
confidence: 99%
“…During wound healing, defects in adipogenesis can abrogate fibroblast recruitment into wound beds, leading to defects in extracellular matrix deposition and tissue repair (3). Migration of adipocyte precursors into the wounded area might also contribute to the mesenchymal repopulation of the wounded site (4) and in wounds where hair follicle neogenesis is observed fully functional adipocyte precursors are present (5). These findings highlight the breadth of the role of adipose tissue in the skin.…”
mentioning
confidence: 86%